Direct in vivo inflammatory cell‐induced corrosion of CoCrMo alloy orthopedic implant surfaces. Issue 1 (26th March 2014) - Gilbert, Jeremy L.; Sivan, Shiril; Liu, Yangping; Kocagöz, Sevi B.; Arnholt, Christina M.; Kurtz, Steven M.
Abstract Cobalt–chromium–molybdenum (CoCrMo) alloy, used for over five decades in orthopedic implants, may corrode and release wear debris into the body during use. These degradation products may stimulate immune and inflammatory responses in vivo. We report here on evidence of direct inflammatory cell‐induced corrosion of human implanted and retrieved CoCrMo implant surfaces. Corrosion morphology on CoCrMo implant surfaces, in unique and characteristic patterns, and the presence of cellular remnants and biological materials intimately entwined with the corrosion indicates direct cellular attack under the cell membrane region of adhered and/or migrating inflammatory cells. Evidence supports a Fenton‐like reaction mechanism driving corrosion in which reactive oxygen species are the major driver of corrosion. Using in vitro tests, large increases in corrosion susceptibility of CoCrMo were seen (40–100 fold) when immersed in phosphate buffered saline solutions modified with hydrogen peroxide and hydrochloric acid to represent the chemistry under inflammatory cells. This discovery raises significant new questions about the clinical consequences of such corrosion interactions, the role of patient inflammatory reactions, and the detailed mechanisms at play. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 211–223, 2015.